Revolutionizing Three-Dimensional Printing: Enhancing Quality Assurance and Point-of-Care Integration through Instrumentation - Javier Suárez-González; Eduardo Díaz-Torres; Cecilia N. Monzón-Rodríguez; Ana Santoveña-Estévez; José B. Fariña (MDPI AG, 2024)
Three-dimensional printing in the field of additive manufacturing shows potential for customized medicines and solving gaps in paediatric formulations. Despite successful clinical trials, 3D printing use in pharmaceutical point-of-care is limited by regulatory loopholes and a lack of Pharmacopoeia guidelines to ensure quality. Semi-solid extrusion is a 3D printing technology that stands out for its versatility, but understanding the fluid dynamics of the semi-solid mass is critical. The aim of this research is to look into the advantages of instrumenting a 3D printer with a semi-solid extrusion motor-driven printhead, which is able to record the printing pressure over time, for in situ characterization of the semi-solid mass and quality evaluation of dosage forms. Four formulations using hydrochlorothiazide as the active pharmaceutical ingredient and several excipients were used. Their flow properties were studied at different printing speeds and temperatures using traditional techniques (rheometer and Texture Analyzer) and the proposed semi-solid extrusion motor-driven printhead incorporated into a printing platform. In addition, the influence of printing speed in the printing process was also evaluated by the study of printing pressure and printlet quality. The results demonstrated the similarities between the use of a Texture Analyzer and the semi-solid extrusion motor-driven. However, the latter enables temperature selection and printing speed in accordance with the printing process which are critical printing parameters. In addition, due to the incorporation of a sensor, it was possible to conclude, for the first time, that there is a link between changes in essential printing parameters like printing speed or formulations and variations in printing pressure and printlet quality attributes such as the energy require to obtain a single dosage unit, weight or diameter. This breakthrough holds a lot of potential for assuring the quality of 3D printing dosage forms and paving the way for their future incorporation into point-of-care settings.